Referenced Approximation Technique for a Rom-Less Sweep Frequency Synthesizer - Atman Jbari; Larbi Bellarbi; Abdelhamid Errachid (Institute of Advanced Engineering and Science, 2016)
The main goal of this paper is to present a novel ROM-less direct digital frequency synthesizer for sweep instrumentation systems. It provides a main sweep channel for frequency analysis and a reference channel for phase and amplitude measurement block operating at constant frequency. For phase to amplitude converter, we propose a new trigonometric approximation technique based on a set of reference angles. In addition, we present the design of the proposed synthesizer and its evaluation in Matlab-Simulink environment. The simulation results illustrate the performances and demonstrate the effectiveness of our proposed circuit.